Interaction study between maltose-modified PPI dendrimers and lipidic model membranes - Wrobel, Dominika; Appelhans, Dietmar; Signorelli, Marco; Wiesner, Brigitte; Fessas, Dimitrios; Scheler, Ulrich; Voit, Brigitte; Maly, Jan (Biochimica et biophysica acta, 2015)
The influence of maltose-modified poly(propylene imine) (PPI) dendrimers on dimyristoylphosphatidylcholine (DMPC) or dimyristoylphosphatidylcholine/dimyristoylphosphatidylglycerol (DMPC/DMPG) (3%) liposomes was studied. Fourth generation (G4) PPI dendrimers with primary amino surface groups were partially (open shell glycodendrimers - OS) or completely (dense shell glycodendrimers - DS) modified with maltose residues. As a model membrane, two types of 100nm diameter liposomes were used to observe differences in the interactions between neutral DMPC and negatively charged DMPC/DMPG bilayers. Interactions were studied using fluorescence spectroscopy to evaluate the membrane fluidity of both the hydrophobic and hydrophilic parts of the lipid bilayer and using differential scanning calorimetry to investigate thermodynamic parameter changes. Pulsed-filed gradient NMR experiments were carried out to evaluate common diffusion coefficient of DMPG and DS PPI in D2O when using below critical micelle concentration of DMPG. Both OS and DS PPI G4 dendrimers show interactions with liposomes. Neutral DS dendrimers exhibit stronger changes in membrane fluidity compared to OS dendrimers. The bilayer structure seems more rigid in the case of anionic DMPC/DMPG liposomes in comparison to pure and neutral DMPC liposomes. Generally, interactions of dendrimers with anionic DMPC/DMPG and neutral DMPC liposomes were at the same level. Higher concentrations of positively charged OS dendrimers induced the aggregation process with negatively charged liposomes. For all types of experiments, the presence of NaCl decreased the strength of the interactions between glycodendrimers and liposomes. Based on NMR diffusion experiments we suggest that apart from electrostatic interactions for OS PPI hydrogen bonds play a major role in maltose-modified PPI dendrimer interactions with anionic and neutral model membranes where a contact surface is needed for undergoing multiple H-bond interactions between maltose shell of glycodendrimers and surface membrane of liposome.
Keywords: Lipid Bilayers; vodíková vazba; lipidové dvojvrstvy; Calorimetry, Differential Scanning; maltosa; fosfatidylglyceroly; difenylhexatrien; Fluorescence Polarization; statická elektřina; Phosphatidylglycerols; Liposomes; fluorescenční polarizace; dimyristoylfosfatidylcholin; diferenciální skenovací kalorimetrie; fluidita membrány; Membrane Fluidity; liposomy; membránové lipidy; Membrane Lipids; Dimyristoylphosphatidylcholine; magnetická rezonanční spektroskopie; Polypropylenes; Hydrogen Bonding; Static Electricity; Maltose; polypropyleny; Magnetic Resonance Spectroscopy; dendrimery; Diphenylhexatriene; Dendrimers; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions